Crosslinkable vegetable oil based natural materials for packaging applications - Ker, Adonica Yan Ting (Nanyang Technological University, 2020)
Biodegradable plastics are gaining popularity in recent years with landfill site becoming increasingly scarce. Combustion of plastics during disposal contributes to air pollution, and low practicality in plastic recycling is the main issue associated with non-degradable plastic usage. Biodegradable plastics can be a promising solution to these problems caused by common non-degradable packaging materials.